Welcome to the hotseat. We've prepared a guide if you'd like to read more about how it works.
0 votes
28 views
in BUS 3024S - Contingencies by (1.6k points)

Hi, could you pleas explain how the (1-y)^-2 is obtained in the solution below. image

1 Answer

+1 vote
by (670 points)
Hi

Please see the last line you attached in the second image. If you differentiate sum (y^k) you will get sum (k*y^k-1). 

So sum (k*y^k-1) = first derivative of sum (y^k) = first derivative of (1-y)^-1 = - (1-y)^-2 *(-1)= (1-y) ^-2
...